Research Growth in the Topic of Soil Liquefaction between Indonesia and New Zealand: A Bibliometric Analysis from Scopus Database - Arif, Maulana; Zulhendra, Riko (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2025)
Soil liquefaction is important in geotechnical engineering, particularly in seismically active areas like Indonesia and New Zealand. With an emphasis on publications written by researchers from Indonesia and New Zealand between 2015 - 2025, This research is a bibliometric analysis that uses data from the Scopus database and the VOS viewer application to assist in interpreting the gathered bibliometric data. The author from New Zealand (Misko Cubrinovski) seems to be the most productive in researching and writing related to soil liquefaction, with 48 articles. Authors from Indonesia are relatively more evenly distributed, with 10-20 articles dominated by Sito Ismanti, Lindung Zalbuin Mase, and Teuku Faisal Fathani. In addition, compared to Indonesian institutions, New Zealand institutions are more likely to collaborate with external parties such as the United States (University of California, University of Texas, University of Washington, etc.), enabling them to obtain greater funding to encourage research productivity. The research map used Scopus RIS data showing three clusters: red (general liquefaction terms), blue (New Zealand-focused, e.g., CPT and shear waves), and green (Indonesia-focused, e.g., seismic response). Minor clusters (purple, yellow) link related topics.